The Role of Brand Equity Mediates The Influence of Endorser Credibility and Brand Experience on Wardah Product Purchase Intention - Mustofa, Mustofa; Irfansyah, Putra; Rifky, Rifky; Curatman, Aang (Green Publisher Indonesia, 2024)
This study is to find out the role of Brand Equity in mediating the influence of Credibility Endorser and Brand Experience on Purchase Intention of wardah products. A study found that endorsers who are considered knowledgeable, reliable, and physically attractive are considered credible. They generate a positive attitude towards the endorsed brand and increase Purchase Intention. The data source used in this study is primary data. Primary data collection was carried out by distributing questionnaires to users of Wardah skincare products in Cirebon City to find out their behavior in making purchases through Google Form. A sample of 150 respondents was used for analysis. data analysis using SmartPLS SEM. Based on the data analysis that has been carried out, Brand Experience and Brand Equity have a positive and significant effect on Purchase Intention, Credibility Endorser has a positive but not significant effect on Brand Equity, and Brand Equity has a positive and significant effect on Purchase Intention, Brand Equity acts as a mediator of the influence of Credibility Endoser and Brand Experience on Purchase Intention. Purchase Intention will be better if Credibility Endorser and Brand Experience are mediated by Brand Equity, meaning that in an effort to increase Purchase Intention, Brand Experience needs to be improved without forgetting Brand Equity which is a mediating variable.